Studi Kritis Atas ???Al-Tafs??r Al-Bay??ni Li Al-Qur?????n Al-Kar??m???Karya ?????isyah ???Abdurrahm??n Bintu Sy??ti??? (W. 1998 M.) - Aghnia Faradits (Program Studi Ilmu Al-Qur'an dan Tafsir, 2022)
Aisyah Abdurrahman or better known as Bintu Syati 'is a very famous female mufassirah in her era. The existence of Amin al-Khulli's style of thought - who is also Bintu Syathi's teacher and husband - made Aisyah Bintu Syathi's preference in explaining or using methods in her interpretation. The book that is in the hands of this author is Bintu Syati's monumental work in the field of interpretation